ANTIBACTERIAL POTENTIAL OF L-TRYPTOPHAN ON EXTENDED-SPECTRUM BETALACTAMASE PRODUCING ESCHERICHIA COLI STRAINS: A PATHOLOGICAL PROMISING APPROACH - Sah, Saroj Kumar; Rasool, Ubaid; B, Shanthi; R, Jayprakash; D, Easwaramoorthy; S, Hemalatha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main aim of this study was to determine the extended-spectrum beta-lactamase (ESBL) production among 83 isolates of Escherichia coli as well as the antibacterial effect of a novel compound, L-Tryptophan Schiff base, on 10 different ESBL positive strains of E. coli. Methods: Phenotypic ESBL activity in E. coli was confirmed by combined disc diffusion test according to clinical laboratory standard institute guidelines. Phenotypically positive ESBL clinical isolates were selected for molecular screening for synchronized detection of blaCTX-M-15 gene. Antibacterial activity of L-Tryptophan Schiff base was evaluated against ESBL positive isolates. The effect of L-Tryptophan Schiff base on a polymerase chain reaction (PCR) amplified a product of CTX-M-15 gene was also evaluated. Results: Antibiotic susceptibility screening showed resistance of ESBL positive isolates in the range of 18–96%. Disc diffusion test for phenotypic ESBL detection revealed that 99% (83/83) of isolates showed resistance to third and fourth generation cephalosporins (ceftazidime, cefotaxime, and cefepime) including ampicillin. L-Tryptophan Schiff base showed antimicrobial effect on E. coli. Molecular analysis for ESBL detection showed that 60% of strains were positive for blaCTX-M-15 gene. L-Tryptophan Schiff base also had downregulating effect on CTX-M-15 gene. Conclusion: This study presented an approach toward finding a suitable drug to reduce the serious infections caused by ESBL positive microorganisms. Phenotypic as well as molecular characterization was performed to get knowledge about the overall behavior of ESBL positive isolates of E. coli. L-Tryptophan Schiff base showed good antibacterial properties against ESBL positive isolates and a downregulating effect on PCR amplified product of CTX-M-15.